Pengaruh Jenis Pelarut pada Ekstraksi Jahe Merah (Zingiber officinale var. rubrum) terhadap Aktivitas Bakteri Penyebab Penyakit pada Hewan Ternak In Vitro - Abdul Zainal Muttaqin; Abun Abun; Endang Sujana (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The use of antibiotics and commercial drugs for handling livestock can have dangerous side effects, so it is necessary to use natural alternative medicines. Red ginger is a potential plant used as traditional medicine. The content of metabolite compounds in red ginger consisting of groups: phenols, terpenoids, essential oils, and flavonoids are reported to be able to inhibit several pathogenic bacteria that cause disease in animals and humans. The purpose of this study was to determine the effect of different types of solvents in the extraction process of red ginger on the activity of disease-causing bacteria in livestock in vitro. Extraction was carried out by maceration method using several solvents consisting of: distilled water, 96% ethanol ethyl acetate, and n-hexane. Antibacterial activity test using agar diffusion method. The parameter tested is the diameter of the inhibition created around the disc paper. The results showed that red ginger extract using ethyl acetate, 96% ethanol, and n-hexane had a diameter of inhibition zone against Staphylococcus aureus bacteria of 3.38 mm; 3.17mm; and 3.70mm. In contrast to Escherichia coli bacteria, all solvents used for red ginger extraction were not found to have an inhibition zone against these bacteria.